Liver Function Test and Diabetes Mellitus: Correlation from a Laboratory Perspective - Aditya Chilay; Neha Mehra; Moumita Misra; Raj Jatale; Shibani Ramchandran (Indian Journal of Medical Biochemistry)
Aims and objectives: To study the correlation of LFTs with DM in the Indian population. Background: Diabetes mellitus (DM) is a metabolic disorder characterized by increased blood glucose levels, resulting from defects in insulin secretion, insulin action, or both. Glucose is an important regulator of various pancreatic β-cell processes, including insulin biosynthesis and release. The liver plays an important role in glucose homeostasis. Evidence of deranged liver functions is observed in long-standing DM and a slight elevation of liver enzymes is seen in insulin resistance. Insulin resistance results in the production of free fatty acids which damage the liver parenchyma and result in elevation of the liver enzymes, such as alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), and gammaglutamyltranspeptidase (GGTP) in the serum. Materials and methods: A retrospective analysis of 46,344 cases over a span of 3 years (2020–2022) was conducted in a referral laboratory in Mumbai. The patients included those who had tested for liver function tests (LFTs) [including SGPT, SGOT, ALP, GGTP, lactate dehydrogenase (LDH)], blood sugar (fasting and post lunch), and HbA1c. Results: Overall 32.11% of the study population was diabetic. Among patients who had done glucose fasting, glucose postprandial, and HbA1c, 17.61% of patients were found to be diabetic at fasting, 15.76% at postprandial and 32.59% had elevated HbA1c levels. Maximum abnormality in LFT was observed in direct bilirubin (18.76%). Multiple logistic regression determined that abnormal ALP [odds ratio (OR): 1.4267, p < 0.0001], abnormal GGTP (OR: 1.87, p < 0.0001), and abnormal SGPT (ALT) (OR: 1.33, p < 0.0001) were independent associates with diabetes. Conclusion: Long-standing or chronic diabetes due to its multisystem affection can adversely affect liver functions. Regulator monitoring of LFTs is essential in diabetic patients to avoid long-term complications.